Effects of Curing Conditions on Shrinkage of Alkali-Activated High-MgO Swedish Slag Concrete - Humad, Abeer M.; Provis, John L.; Cwirzen, Andrzej (Frontiers in Materials, 2019)
This study aimed to determine the effects of curing regime on shrinkage of alkali-activated concretes produced from a Swedish high-MgO blast furnace slag. Sodium carbonate (SC), sodium silicate (SS), and their combination were used as alkali activators. The studied curing procedure included heat-treatment, no heat-treatment, sealed and non-sealed conditions. The heat curing increased the compressive strengths of the concretes activated with SS and with the combination of SS and SC. Sealed-curing applied for a period of 1 month reduced the measured drying shrinkage by up to 50% for all studied heat-treated samples. Conversely, the same curing procedure significantly increased the development of the drying shrinkage once the seal was removed after 28 days of curing in the case of the SC-activated concretes non-heat treated. Higher degree of reaction/hydration reached by the binders in these concretes was indicated as the main factor. All of the concretes studied had showed a significant microcracking of the binder matrix, with the most extensive cracking observed in the sealed lab-cured mixes. The heat-cured mixes activated with SS and combination of SC and SS showed the most homogenous microstructure and low extensive micro cracking comparing with lab-cured ones.